2008
DOI: 10.1002/eqe.779
|View full text |Cite
|
Sign up to set email alerts
|

Seismic self‐centering steel beam‐to‐column moment connections using bolted friction devices

Abstract: SUMMARYThis paper first presents the force-deformation relationship of a post-tensioned (PT) steel beam-to-column connection constructed with bolted web friction devices (FDs). This paper then describes the test program conducted in the National Center for Research on Earthquake Engineering, Taiwan, on four bolted FDs and four full-scale PT beam-to-column moment connection subassemblies using the FDs. Tests confirm that (1) the hysteretic behavior of four bolted FDs is very stable, (2) the friction coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(55 citation statements)
references
References 6 publications
(20 reference statements)
1
49
0
Order By: Relevance
“…Steel self-centering moment-resisting frames (SC-MRFs) using post-tensioned (PT) beam-column connections are a promising class of resilient structures that exhibit softening force-drift behavior and eliminate beam inelastic deformations and residual drifts (Ricles et al 2001;Christopoulos et al 2002;Rojas et al 2004;Kim and Christopoulos 2008a;Tsai et al 2008;Chou and Lai 2009;Wolski et al 2009;Vasdravellis et al 2013a,b;Dimopoulos et al 2013). Seismic design procedures for SCMRFs are proposed in (Garlock et al 2007;Kim and Christopoulos 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Steel self-centering moment-resisting frames (SC-MRFs) using post-tensioned (PT) beam-column connections are a promising class of resilient structures that exhibit softening force-drift behavior and eliminate beam inelastic deformations and residual drifts (Ricles et al 2001;Christopoulos et al 2002;Rojas et al 2004;Kim and Christopoulos 2008a;Tsai et al 2008;Chou and Lai 2009;Wolski et al 2009;Vasdravellis et al 2013a,b;Dimopoulos et al 2013). Seismic design procedures for SCMRFs are proposed in (Garlock et al 2007;Kim and Christopoulos 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Several configurations of self-centering MRFs have been proposed, with the main difference being relevant to the type of energy dissipating device used, i.e. steel yielding based [20][21][22][23][24][25] or friction based [26][27][28][29]. Christopoulos et al [30] proposed a braced frame using self-centering braces.…”
Section: And Uangmentioning
confidence: 99%
“…A variety of friction dissipators have been proposed for structural energy dissipation (Pall and Marsh 1982, Palsson et al 1984, Tyler 1985, Sumitomo 1987, Pall 1989, Richter et al 1990, Vezina et al 1992, Cherry and Filiatrault 1993, Grigorian et al 1993, Way 1996, Soong and Dargush 1997, Housner et al 1997, Wu and Ou 2003, Cho and Kwon 2004, Morgen and Kurama 2004, Tsai et al 2008, Morgen and Kurama 2008, design criteria have been issued (Rao et al 1996, Colajanni and Papia 2008, Levy et al 2000, Moreschi and Singh 2003, De la Llera et al 2005, Levy, Lavan and Rutenberg 2005, numerical simulation algorithms have been formulated (Dimova et al 1995, De la Cruz et al 2007) and a number of applications have been reported (Pall et al 1993, Tena 2007, Zhou et al 2007). In the reference (Dimova and Hirata 2000) a study about the seismic efficiency of friction dissipators is presented.…”
Section: Fig 2 Hysteresis Loops Of Energy Dissipatorsmentioning
confidence: 99%
“…-Reported experiments (Tyler 1985, Filiatrault and Cherry 1987, Fitzgerald et al 1989, Anagnostides and Hargreaves 1990, Aiken and Kelly 1990, Richter et al 1990, Whittaker et al 1991, Grigorian et al 1993, Yang and Popov 1995, Wu and Ou 2003, Morgen and Kurama 2004, Ng and Xu 2006, Vial et al 2005, Ricles et al 2006, Zhu et al 2006, Tsai et al 2008, Morgen and Kurama 2008, Iyama et al 2009) do not yield enough information about those questions, as they are mostly oriented to check the global validity of particular devices or assemblies. -The numerical simulation constitutes a challenging issue as the dynamic behavior of friction devices is highly nonlinear, as discussed previously.…”
Section: Fig 2 Hysteresis Loops Of Energy Dissipatorsmentioning
confidence: 99%